An institutional arrangement analysis of the South African Bureau of Standards - Makhuvela, Ayender Ndzalama (My University, 2020)
The aim of the research is to analyse the institutional arrangements of the verification network institutions for local content requirements and designation policy in South Africa (SA). The verification network institutions for local content requirements and designation policy in South Africa hardly receive scholarly scrutiny. This study is undertaken to understand the institutional arrangements, and the procedural, methodological and institutional value choices that are in place to capacitate the South African Bureau of Standards (SABS) to conduct local content verification. A Qualitative research methodology approach is undertaken to study inductive reasoning and to answer the research questions that require discussion and elaboration by research participants. This research arises from the need to gain further insights into the capacity challenges the SABS is experiencing in conducting verifications. The primary data was collected using methods of observations, content analysis, structured and unstructured interviews with stakeholders from government departments, the industry supplying products and goods, procuring entities participating in the procurement of public goods and services. Further, the secondary data is generated from theoretical analysis. The mandate of the SABS is defined by the Standards Acts (1945;1993;2008) that established the institution as a statutory Standards Authority. It was enacted as a national institution for the development, promotion and maintenance of standards on behalf of the South African government. Each Act repealing the previous is about the continuation of service, updating the rules for human conduct, complying with the governance requirement of the government. The SABS aligned its mandate to support governments Industrial Policy Action Plan (IPAP), which is the government’s plan for industrialization that promotes localization of products and services, protecting the local industries from penetration of low-quality cheap imports. The SABS were appointed by the dti during the amendments to the procurement policy due to the expertise and the fact that the SABS prepared the SATS document. It was then recommended that the SABS be the verification authority for local content and designation policy. There was no MOU or any legal official documentation detailing the mandate of the institutions to conduct the verification. This verification process has been faced with conceptualisation and implementation challenges of cost and also non-compliance by the procuring entities. The cost of verification has been a contentious issue since inception of the policy. This resulted in gaps in the delegated authority and the funding of the institution to conduct verification. Certain functions are more constructive when handled by particular state institutions, as certain institutions are great agents of institutional design, but not-so-great agents of implementation and enforcement. The SABS has been delegated legal powers to conduct verification by the dti, using the PPPFA. However, these powers are not enforceble as the procuring entity is the one that enters into contractual agreement with the bidders who will be verified. Additionally, the procuring entities have been empowered to action remedial action against a tenderer who submitted false information. Institutional change is necessary to improve service delivery and achieving the organisational mandate, goals and objective. In reforming institutions, it is necessary to formally change the institutional arrangement such as re-organisation of the administrative functions in the institution. The Minister of Trade and Industry exercised his discretion as stated in the Standards Act of 2008 Subsection 9 and terminated the term of office for board members. By placing the institution under administration dissolving the board citing “institutional failures, in governance, finances, policy and operation. This can be seen as a form of institutional reform as there was a formal change to the institutional arrangement of the SABS
A research report submitted to the School of Governance in the Faculty of Commerce, Law and Management of the University of Witwatersrand, Johannesburg, South Africa, in part fulfilment of the requirements for the Degree of the Master of Management in Public Policy, 2020
Keywords: UCTD; Institutional arrangement; Procedural; Methodological and institutional value choices; Institutional theory; New Sociological institutionalism; SDG-8: Decent work and economic growth